Teacher emotional intelligence during virtual teaching by confinement - Ordaz Villegas, Gabriela; Durán Fonseca, Thamir Danir Danulkán (IE Revista de Investigación Educativa de la REDIECH, 2023)
The abrupt change of teaching, from face-to-face to virtual, generated in elementary teachers excess workload, a perception of neglecting their personal and family activities, uncertainty about health, as well as emotional exhaustion. Considering that emotional intelligence can act as a personal protective factor, the objective of this study was to evaluate the differences between teachers in a virtual teaching situation due to confinement from COVID-19, according to various conditions –sex, years of teaching experience, educational level where they teach, and type of school–, regarding the components of emotional intelligence: attention, clarity and repair. A quantitative comparative study was carried out, with a non-probabilistic sample made up of 103 teachers, with an average age of 41.31 years (SD = 9.78), 41.7% men and 58.3% women. The 24-item Trait Meta-Mood Scale instrument was used. Through anova with factorial design, interaction effects were found in emotional comprehension and regulation, in relation to some characteristics of the teacher. These findings point to the need to consider the development of emotional skills in the educational field to better face future adversities.